Exploring the potential of nest archives for establishing long-term trends in local populations of an Arctic-nesting colonial sea duck - Inmaculada Álvarez-Manzaneda; Kathleen M. Rühland; Marlo Campbell; Matthew P. Duda; Mark L. Mallory; Nik Clyde; H. Grant Gilchrist; Kathryn E. Hargan; John P. Smol (PLoS ONE, 2025)
Tracking changes in seabird populations from remote Arctic regions using traditional monitoring techniques is financially and logistically challenging, leading to limited information on historical population trends. In this pilot study, we use a novel application of paleolimnological proxies to track environmental change using bird nests. Specifically, we examine long-term population dynamics of the Northern Common Eider (Somateria mollissima borealis), a philopatric sea duck. Eider nests from the Canadian sub-Arctic were sampled and radioisotopically dated, indicating that eiders have been nesting here since the 1800s. To assess the applicability of paleoecological proxies in nests to monitor environmental changes and long-term eider population dynamics, we examined changes in diatom species composition, shifts in the abundance of siliceous proxies (i.e., diatoms, chrysophyte cysts, phytoliths, protozoan plates), visible reflectance spectroscopy-inferred chlorophyll a (VRS-chla), stable nitrogen isotopes, and a selection of metal(loid)s. Warmer post-Little Ice Age conditions after the mid-19th century, together with higher eider occupation rates, promoted the proliferation of diatoms and other siliceous indicators. Declining eider populations during the industrial era, likely due to increased hunting pressures, was indicated by declines in δ15N values and relative abundances of diatom taxa typically associated with higher nutrients and/or moisture. Increasing concentrations of metals (i.e., Zn and Cd), δ15N values, and VRS-chla, which are positively associated with eider nesting activity, provided further support that eider numbers increased during the latter part of the 20th century. Our study shows that the accumulated vegetative and peat material from eider nests can provide a powerful tool to track historical bird population dynamics in ways that traditional, more recent, population monitoring methods cannot. Collectively, these methods can contribute insights to guide conservation decisions of this harvested species and other under-surveyed species.